The Cameroon Public Service and Career Choice Management: From a Cognitive Dissonance Perspective - Tachi , Nkwanui Musa (Journal of Innovation in Education and Social Research, 2025)
The head of state of Cameroon, his Excellency president Paul Biya in his speech to the youths each year, reminds the youths to be actively engaged in self-employment careers. Despite this call, most youths still crave to adhere to the public service. With this mind-set, most of them failed to carry out career choice preparedness effectively.This article sets out to investigate the impact of the Cameroon public service on the youth career choice management on one hand, and on the other hand, to mitigate this impact through the application of some proposed career choice management strategies. This is a quantitative type of research with a cross-sectional survey study design carried out using the non-experimental method.Our instrument for data collection is the five-point Likert questionnaires and our study population are the student-teachers of Enieg and Eniet in the Wouri division of the littoral region. The technique used for data analysis is the descriptive statistic carried out using the SPSS software version 20. The findings show that two major attributes of the Cameroon public service influence youths’ career choice management. These attributes in the prevailing order were determined to be the civil servants’ professional status, the civil servants’ financial status,(Borchert, 2002, kouatchou, 2023). Career choice management strategies can be used to reinforce self-efficacy skill that will have implications for future career planning.